Biotechnology in the mirror of ethics - SM Seyed Fatemi (JRI, 2002)
Bioethics seems to be the most important branch of applied ethics. It concerns both philosophers and scientists. Such crucial questions as health care, ART, genetic engineering, abortion, euthanasia, suicide, trasplanation, population issues, animal rights and the like are just examples of questions are being dealt with in this decipline. Due to special nature of these questions, to offer a sufficient moral theory, in addition to seven criteria of applicability i.e., clarity, completeness, comprehensiveness, practicability as well as justificatory, output and explanatory powers, an internal urging power is needed. And that may be achieved by divine persuasion to follow rational moral principles which are comprehensible by human faculty. Accordingly, in the level of content moral principles are rational norms, but in the level of implementation divine command is an urging motivation to persuade human agents to act morally. And by this, we would have a non-divine command moral theory which gives considerable role to religious beliefs. Also in this article in addition to dealing with main moral theories, Kantian, utilitarianism, virtue ethics and religious approach to biotechnological issues and their implications in this field, I have offered certain moral principles which can be applied as guiding principles biotechnological questions.
Keywords: Bioethics, Ethical principles, Divin command theory, Kantian theory, Utilitarianism, Virtue Ethics